Book Reviews (Historia, 2021)
1. Hermann Giliomee: Die Kaap tydens die Eerste Britse Bewind 1795-18032. Louis Cohen: Reminiscences ofJohannesburg and London3. H.M. Hole: Old Rhodesian Days4. A.J. Venter: Coloured - a profile of two million South Africans5. Anna de Villiers: Barrewets oor Drakensberg6. Stephan Viljoen: Economic System in World History7. Gerald Shaw: Some beginnings, The Cape Times, 1876-19108. Doreen Lamb: The Republican Residents9. F.A. van Jaarsveld: Probleme by die Ondemgmn Geskiedenrj10. L.G. Brandon: History, A Guide to Admnced Study11. E.G. Davis: The First Sex12. A.M. Josephy: The Indian Heritage of Americ`13. C.C. Eloff (red.): 00rlo~;dogboekie mn H.S. Oosterhogen14. M. Schoonraad: Walter Battis